2021
DOI: 10.1371/journal.pone.0253871
|View full text |Cite
|
Sign up to set email alerts
|

Two novel truncating variants in UBAP1 are responsible for hereditary spastic paraplegia

Abstract: Hereditary spastic paraplegias (HSPs) are a group of rare neurodegenerative disorders. HSPs are complex disorders and are clinically and genetically heterogeneous. To date, more than 80 genes or genetic loci have been reported to be responsible for HSPs in a Mendelian-dependent manner. Most recently, ubiquitin-associated protein 1 (UBAP1) has been recognized to be involved in HSP. Here, we identified novel protein truncating variants in two families with pure form of HSP. A novel deletion (c.468_469delTG) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…According to results reported before, brain MRI was normal in most patients except for one who presented with mild generalized cortical-subcortical volume loss. Moreover, electromyography results of all the patients were normal (6)(7)(8)(9)(12)(13)(14). The clinical features of SPG80 probands with UBAP1 mutations are summarized in Figure 2.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…According to results reported before, brain MRI was normal in most patients except for one who presented with mild generalized cortical-subcortical volume loss. Moreover, electromyography results of all the patients were normal (6)(7)(8)(9)(12)(13)(14). The clinical features of SPG80 probands with UBAP1 mutations are summarized in Figure 2.…”
Section: Discussionmentioning
confidence: 96%
“…To date, a total of twenty heterozygous UBAP1 mutations have been identified among 91 patients from 35 families worldwide and diagnosed as SPG80 (including this one). Nineteen mutations (c.247_248insGTGAATTC, c.279delG, c.286_290dupCCAGA, c.295dupG, c.312delC, c.324_325delCA, c.361dupC, c.373C>T, c.382delA, c.425_426delAG, c.426_427delGA, c.436_437insTGAG, c.468_469delTG, c.437dupG, c.475_476delTT, c.512T>G, c.526G>T, c.535G>T, and c.1091delC) have been reported ( 6 9 , 12 14 ), while our mutation (c.371dupT) was undocumented before ( Figure 1F ). Among the 20 mutations, 16 were frameshift ones identified in 67 patients, of which 53 showed a pure type, 12 showed a complicated type, and 2 were asymptomatic cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, 18 UBAP1 variants including the one identified here have been described (Bian et al, 2021;Bourinaris et al, 2020;Gu et al, 2020;Wang et al, 2020), and 17 of them occurred in Exon 4 of UBAP1 (Figure 1g), implying that Exon 4 is a potential hotspot region of UBAP1. In addition, all identified variants preserve the UMA domain but cause a loss of the SOUBA domain, implying that loss of ubiquitin binding would be detrimental.…”
mentioning
confidence: 79%
“…It was also found that UBAP1 interacted with Toll/interleukin 1 receptor (TIR) domain-containing protein of Pseudomonas aeruginosa , and played a major role in virulence of bacterial pathogens Imbert et al (2017) . Recently, the mutations in UBAP1 were found to cause the pure or complex HSP with autosomal dominant inheritance ( Farazi Fard et al, 2019 ; Lin et al, 2019 ; Nan et al, 2019 ; Bourinaris et al, 2020 ; Gu et al, 2020 ; Wang et al, 2020 ; Bian et al, 2021 ). Therefore, UBAP1 was known as the pathogenic gene of spastic paraplegia-80 (SPG80, OMIM No.…”
Section: Introductionmentioning
confidence: 99%